Sociocultural pressures and appearance ideal internalization: Their impact on body dissatisfaction in Brazilian adults - Camila Carla Souza do Prado; Maria Cláudia Bernardes Spexoto; Wanderson Roberto da Silva; Deise Bresan; Bruna Menegassi (Preventive Medicine Reports)
Objective: To analyze the relationship between internalization of appearance ideals, sociocultural pressures, and body dissatisfaction among Brazilian adults. Methods: A cross-sectional study was conducted in Mato Grosso do Sul, Brazil, between January and December 2023. Using convenience sampling, data were collected from 290 adults (18–64 years old; median age = 24.0, IQR25 = 21.0, and IQR75 = 34.0; 69.3 % female) through an online self-report questionnaire. The dependent variables included socioeconomic, demographic, and anthropometric data. Sociocultural pressures and the internalization of appearance ideals were measured using the SATAQ-4, with body dissatisfaction as the independent variable. Statistical analyses involved non-parametric tests (Kolmogorov-Smirnov, Mann-Whitney U, Kruskal-Wallis, Dunn's post hoc tests) and Spearman's correlation, with a significance level set at p < .05. Results: Body dissatisfaction was 84.5 % prevalent. Dissatisfaction related to excess weight was associated with pressure from family (p < .001), friends (p = .001), the media (p < .001), and internalization of the thin ideal (p < .001). The median ideal athletic/muscular body was significantly higher in males than in females (p = .015), while median media pressure was higher in females compared to males (p = .001). Conclusions: The study highlights the role of sociocultural pressures and appearance ideals in body dissatisfaction, supporting the Tripartite Influence Model.